Severe Acute Respiratory Syndrome Coronavirus 2 Neutralizing Antibody Titers in Convalescent Plasma and Recipients in New Mexico: An Open Treatment Study in Patients With Coronavirus Disease 2019. (11th August 2020) - Bradfute, Steven B; Hurwitz, Ivy; Yingling, Alexandra V; Ye, Chunyan; Cheng, Qiuying; Noonan, Timothy P; Raval, Jay S; Sosa, Nestor R; Mertz, Gregory J; Perkins, Douglas J; Harkins, Michelle S
Abstract: Background: Convalescent plasma (CP) is a potentially important therapy for coronavirus disease 2019 (COVID-19). However, knowledge regarding neutralizing antibody (NAb) titers in donor plasma and their impact in patients with acute COVID-19 remains largely undetermined. We measured NAb titers in CP and in patients with acute COVID-19 before and after transfusion through the traditional Food and Drug Administration investigational new drug pathway. Methods: We performed a single-arm interventional trial measuring NAb and total antibody titers before and after CP transfusion over a 14-day period in hospitalized patients with laboratory-confirmed severe acute respiratory syndrome coronavirus 2 infection. Results: NAb titers in the donor CP units were low (<1:40 to 1:160) and had no effect on recipient neutralizing activity 1 day after transfusion. NAb titers were detected in 6 of 12 patients on enrollment and in 11 of 12 at ≥2 time points. Average titers peaked on day 7 and declined toward day 14 ( P = .004). Nab titers and immunoglobulin G levels were correlated in donor plasma units (ρ = 0.938; P < .001) and in the cumulative patient measures (ρ = 0.781; P < .001). Conclusions: CP infusion did not alter recipient NAb titers. Prescreening of CP may be necessary for selecting donors with high titers of neutralizing activity for infusion into patients with COVID-19. Clinical Trials Registration: NCT04434131. Abstract : We observed low neutralizing antibody (NAb) levels in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) convalescent plasma (CP), and CP administration did not affect NAb levels in recipients with SARS-CoV-2. CP NAb levels should be assessed before infusion in patients.